High temperature resistant separator

JP2025026784APending Publication Date: 2025-02-25BENQ MATERIALS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023202240
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-11
Filing Date
2023-11-29
Publication Date
2025-02-25

AI Technical Summary

Benefits of technology

【0024】 本発明の利点、特徴、および達成された技術的方法は、例示的な実施形態を参照してより詳細に説明されるので、より理解しやすくなる。本発明は、異なる形式で実現されることができるので、本明細書に記載された実施形態に限定されると理解されるべきではない。または対照的に、提供される実施形態は、通常の知識を有する当業者にとって、本発明の範疇をより徹底的に、完全的に、全面的に伝えることになる。本発明は添付された特許出願の範囲にのみ定義される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025026784000002
    Figure 2025026784000002
  • Figure 2025026784000003
    Figure 2025026784000003
  • Figure 2025026784000004
    Figure 2025026784000004
Patent Text Reader

Abstract

To provide a high temperature resistant separator that is resistant to curling and deformation.SOLUTION: A high temperature resistant separator includes a porous membrane having a polyolefin porous substrate and an inorganic layer, and a thermally strengthened layer formed on the surface of the porous membrane and the inner wall of the porous structure. The inorganic layer includes a plurality of inorganic particles and an adhesive, and is formed on at least one surface of the polyolefin porous substrate. The polyolefin porous substrate and the inorganic layer have a plurality of porous structures that are in communication with each other. The thermally strengthened layer is a composite layer formed by crosslinking titanium alkoxide and a photoreactive agent with the polyolefin and / or the adhesive on the surface of the porous membrane and the inner wall of the porous structure.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a high temperature resistant separator, and more particularly to a high temperature resistant separator having a heat strengthening layer. [Background technology]

[0002] During operation of a lithium-ion battery, if it is used improperly or damaged by external forces in a high-temperature application environment, the electrochemical reaction inside the battery may become abnormal and the temperature may rise. The separator in the battery is often made of polyolefin as the base material, and when the melting point exceeds about 130°C, it begins to soften, causing thermal runaway with the decomposition of the active material of the electrode, and the temperature may rise rapidly, causing shrinkage and deformation, or the membrane may melt and break. At higher temperatures, the positive and negative electrodes are not sufficiently isolated, and a short circuit continues to form, accelerating the electrochemical reaction rate and causing greater damage.

[0003] It is well known that the heat shrinkage rate can be reduced by adopting a crosslinkable polyolefin substrate with a higher melt rupture temperature or adding an inorganic coating layer on the surface and / or pore walls of the separator to improve the integrity of the separator. However, even if the polyolefin substrate has crosslinking properties to increase the upper limit of the melt rupture temperature, there is a limit to the improvement of the high-temperature heat shrinkage rate for the polymer segment that has reached the melting point or higher and softened. In addition, since the polyolefin substrate is often formed into a porous membrane by uniaxial or biaxial stretching, it is difficult to maintain the same stretch ratio in the stretching direction and the width direction in the manufacturing process. Therefore, when it is subjected to heat shrinkage, it will curl and still not have the effect of sufficiently isolating the electrodes. The separator having an inorganic coating layer must have a certain content of inorganic particles or more to effectively reduce its heat shrinkage rate. However, in the conventional inorganic coating layer, the inorganic particles are bonded with an adhesive and need to be applied to the surface of the separator, so that too many inorganic particles may block the holes in the separator and the internal electrical resistance may be too high. In addition, due to the inconsistency in the shrinkage rates of the inorganic particles, adhesive, and polyolefin substrate in the inorganic coating layer at high temperatures, the inorganic coating layer on the surface or the entire isolating film may still crack, and the electrochemical reaction cannot continue to occur at high temperatures.

[0004] In the manufacturing process of polyolefin separator, a known technique is proposed, which is to coat a polyolefin porous membrane with a hydrogen-substituted photoinitiator, and then form cross-linking on the porous membrane surface after irradiation, or to add a photoinitiator to an inorganic coating layer and coat it on a porous substrate. However, although these proposals can improve the melt fracture temperature of the porous membrane, they do not have the desired effect on the high-temperature thermal shrinkage of the membrane material.

[0005] Therefore, a high temperature resistant separator having good heat shrinkability is required. Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention discloses a high-temperature resistant separator, which has a high melt rupture temperature and low heat shrinkage at high temperatures, and the heat shrinkage rates in all directions at high temperatures are consistent, so that it is not easily curled. [Means for solving the problem]

[0007] The high-temperature resistant separator of the present invention includes a porous membrane having a polyolefin porous substrate and an inorganic layer, and a heat-strengthening layer formed on the surface of the porous membrane and the inner wall of the porous structure. The inorganic layer includes a plurality of inorganic particles and an adhesive, and is formed on at least one surface of the polyolefin porous substrate. The polyolefin porous substrate and the inorganic layer have a plurality of porous structures that are in communication with each other. The heat-strengthening layer is a composite layer formed by crosslinking titanium alkoxide and a photoreactive agent with the polyolefin and / or adhesive on the surface of the porous membrane and the inner wall of the porous structure.

[0008] In the high temperature resistant separator according to one embodiment of the present invention, the thermal shrinkage rate in each direction after being left at 180° C. for 1 hour is less than 1%.

[0009] In the high temperature resistant separator according to one embodiment of the present invention, the titanium alkoxide is methanol titanium, ethanol titanium, isopropanol titanium, or a combination thereof.

[0010] In another embodiment of the high temperature resistant separator of the present invention, the photoreactor is 2-isopropylthioxanthone, thioxanthone, a thioxanthone derivative, or a combination thereof.

[0011] In another embodiment of the high-temperature resistant separator of the present invention, the polyolefin porous substrate is a single-layer or multi-layer porous substrate of polyethylene, polypropylene or a copolymer thereof.

[0012] In another embodiment of the high-temperature resistant separator, the inorganic layer contains 80 to 99% by weight of inorganic particles, contains 1 to 20% by weight of adhesive, and has a thickness of 0.5 μm to 5 μm, preferably 0.5 μm to 3 μm.

[0013] In another embodiment of the high temperature resistant separator, the inorganic particles of the inorganic layer are Al2O3, Al(OH)3, boehmite (AlOOH), TiO2, SiO2, Mg(OH)2, BaSO4, BaTiO3, SrTiO3, HfO2, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, SiC, B4C, AlN, BN, Si3N4, TiN, or a combination thereof.

[0014] In the high-temperature resistant separator according to the present invention, the inorganic particles have an average particle size (D50) of 0.1 μm to 2.0 μm.

[0015] In another embodiment of the high-temperature resistant separator, the adhesive of the inorganic layer is ethylene-vinyl acetate copolymer (EVA), polyacrylonitrile, polyacrylic acid and its derivatives, poly(meth)acrylate, crosslinkable (meth)acrylic resin, polyacrylamide (PAM), fluorine-based rubber, styrene-butadiene rubber (SBR), methylol cellulose, hydroxyethyl cellulose, polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyvinylpyrrolidone (PVP), poly-N-vinyl acetamide, polyvinylidene fluoride (PVDF), polyurethane, or a combination thereof.

[0016] In another embodiment of the high temperature resistant separator, the heat strengthening layer further comprises a crosslinking coagent selected from the group consisting of divinylbenzene, bisphenol A dimethyl acrylate, bisphenol A epoxy diacrylate, triallyl cyanurate, triallyl isocyanurate, pentaerythritol triallyl ether, butadiol diacrylate, ethylene glycol diacrylate, and combinations thereof.

[0017] Another aspect of the present invention provides a method for producing a high-temperature resistant separator. The method includes providing a porous membrane, preparing a thermally strengthened precursor solution, applying the thermally strengthened precursor solution to the porous membrane, and irradiating ultraviolet light to form a thermally strengthened layer on the surface of the porous membrane and the inner wall of the porous structure. The porous membrane has a polyolefin porous substrate and an inorganic layer. The inorganic layer includes a plurality of inorganic particles and an adhesive. The inorganic layer is formed on at least one surface of the polyolefin porous substrate. The polyolefin porous substrate and the inorganic layer have a plurality of porous structures that are in communication with each other. The thermally strengthened precursor solution includes 600 ppm to 3000 ppm of titanium alkoxide and 150 ppm to 1500 ppm of photoreactive agent. The thermally strengthened layer is a composite layer formed by crosslinking the titanium alkoxide and the photoreactive agent with the polyolefin and / or adhesive on the surface of the porous membrane and the inner wall of the porous structure.

[0018] In the method for preparing a high-temperature resistant separator according to the present invention, the titanium alkoxide in the thermal strengthening precursor solution is methanol titanium, ethanol titanium, isopropanol titanium or a combination thereof, and the solvent is methanol, ethanol, isopropanol or a combination thereof.

[0019] In the method for preparing a high-temperature resistant separator according to the present invention, the photoreactant in the thermally strengthened precursor solution is 2-isopropylthioxanthone, thioxanthone, a thioxanthone derivative, or a combination thereof.

[0020] In the method for preparing a high-temperature resistant separator according to the present invention, the thermally strengthened precursor solution further comprises a cross-linking coagent, which is selected from the group consisting of divinylbenzene, bisphenol A dimethyl acrylate, bisphenol A epoxy diacrylate, triallyl cyanurate, triallyl isocyanurate, tetrapentaerythritol triallyl ether, butadiol diacrylate, ethylene glycol diacrylate, and combinations thereof.

[0021] The above summary of the invention is intended to provide a simplified summary of the disclosure so that readers have a basic understanding of the disclosure. This summary of the invention is not a complete summary of the disclosure, and is not intended to present important / critical elements of the embodiments of the present invention or to define the scope of the present invention. After referring to the following embodiments, those skilled in the art to which the present invention pertains can easily understand the basic spirit of the present invention and the technical means and embodiments adopted by the present invention. [Brief description of the drawings]

[0022] [Figure 1a] 1 is an appearance image of a separator according to a comparative example of the present invention after a high-temperature crack test. [Figure 1b] 1 is an appearance image of a separator according to a comparative example of the present invention after a high-temperature crack test. [Diagram 2] 1 is an appearance image of a high-temperature resistant separator according to an embodiment of the present invention after a high-temperature crack test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] In order to make the disclosure of the present invention more detailed and complete, the following describes the embodiments and specific examples of the present invention. However, this is not the only way to implement or operate the specific embodiments of the present invention. The embodiments disclosed below may be combined with each other when beneficial, may be substituted, or may be added to other examples. No further description or explanation is required.

[0024] The advantages, features, and technical methods achieved by the present invention will be more easily understood as they are described in more detail with reference to exemplary embodiments. The present invention can be realized in different forms, and therefore should not be understood to be limited to the embodiments described herein. Or, on the contrary, the embodiments provided will convey the scope of the present invention more thoroughly, completely, and comprehensively to those skilled in the art. The present invention is defined only by the scope of the attached patent application.

[0025] Unless otherwise defined, all terms (including technical and scientific terms) and proper nouns used in the following text have substantially the same meaning as commonly understood by those skilled in the art to which the present invention belongs. For example, terms defined by commonly used dictionaries should be understood to have a meaning consistent with the content of the relevant field. Unless explicitly defined in the following text, they should not be understood in an overly idealized or overly formal sense.

[0026] The present invention provides a high-temperature resistant separator. The high-temperature resistant separator includes a porous membrane having a polyolefin porous substrate and an inorganic layer, and a heat-strengthening layer formed on the surface of the porous membrane and the inner wall of the porous structure. The inorganic layer includes a plurality of inorganic particles and an adhesive, and is formed on at least one surface of the polyolefin porous substrate. The polyolefin porous substrate and the inorganic layer have a plurality of porous structures that are in communication with each other. The heat-strengthening layer is a composite layer formed by crosslinking titanium alkoxide and a photoreactive agent with the polyolefin and / or the adhesive on the surface of the porous membrane and the inner wall of the porous structure.

[0027] The high-temperature resistant separator of the present invention is obtained by directly forming a heat-strengthened layer on the surface of the porous membrane and the inner wall of the porous structure to obtain a high-temperature resistant separator, which enhances the resistance ability and structural integrity under high temperatures. Due to this heat-strengthened layer, the high-temperature resistant separator of the present invention has a high melt fracture temperature, puncture resistance after high temperatures, and low heat shrinkage at high temperatures, and the heat shrinkage rates in all directions at high temperatures are consistent, so it is not easily curled.

[0028] The heat-strengthening layer of the high-temperature resistant separator of the present invention is a composite layer formed by applying a heat-strengthening precursor solution containing titanium alkoxide and a photoreactive agent onto a porous membrane, irradiating it with ultraviolet light, and then crosslinking it with the polyolefin and / or adhesive on the surface of the porous membrane and the inner wall of the porous structure.

[0029] In order to make the polyolefin porous substrate having saturated and stable carbon bonds reactive and participate in crosslinking, a photoreactive agent that dehydrogenates by ultraviolet light irradiation to generate free radicals and a polyolefin porous substrate having carbon bonds containing hydrogen atoms can be used. The carbon bonds on the surface of the polyolefin porous substrate also form free radicals together to form a crosslinking reaction on the surface of the polyolefin porous substrate having saturated and stable carbon bonds. The high-temperature-resistant separator according to the present invention includes a titanium alkoxide having a carbon bond containing a hydrogen atom and an adhesive in addition to a polyolefin porous substrate and a photoreactive agent, so that when irradiated with ultraviolet light of sufficient energy, the hydrogen-containing carbon bonds contained in the surface layer of the polyolefin porous substrate, the photoreactive agent, the titanium alkoxide, and the adhesive in the inorganic layer can all generate reactive free radicals to carry out a crosslinking reaction. A composite layer crosslinked by polyolefin, photoreactive agent, titanium alkoxide, and / or adhesive is formed on the surface layer of the porous membrane and the inner wall of the porous structure. The titanium alkoxide reacts in an alcohol-based solvent to form titanium oxide, part of which is close to the structure of the inorganic particles, thereby enhancing the stability of the covalent bond structure of the inorganic particles. Furthermore, the covalent bond structure of inorganic particles (for example, oxides and hydroxides including various metals and silicones) is not destroyed by irradiation with ultraviolet light.

[0030] In the high temperature resistant separator according to one embodiment of the present invention, the titanium alkoxide contained in the thermal strengthening layer may be a titanium alkoxide having a carbon bond containing a hydrogen atom, such as methanol titanium, ethanol titanium, isopropanol titanium, or a combination thereof.

[0031] In another embodiment of the high temperature resistant separator, the photoreactor is 2-isopropylthioxanthone, thioxanthone, a thioxanthone derivative, or a combination thereof, which is used to dehydrogenate a carbon bond containing a hydrogen atom to form a free radical.

[0032] In yet another embodiment of the present invention, in the high-temperature resistant separator, the thermal strengthening layer is a composite layer formed on the surface of the porous membrane and the surface of the inner wall of the porous structure by crosslinking titanium alkoxide and photoreactive agent with the polyolefin porous substrate of the porous membrane and the adhesive of the inorganic layer through free radical reaction.This does not require the deposition of too high a concentration (≦3000 ppm) of titanium alkoxide in the form of oxide on the surface of the inorganic layer and the inner wall of the porous structure, and can obtain better thermal stability.

[0033] In another embodiment of the high-temperature resistant separator, since it has a heat-strengthened layer with a crosslinked composite structure, the heat shrinkage in each direction after being left at 180°C for 1 hour can be less than 1%. Here, the "heat shrinkage in each direction" includes the heat shrinkage in the main stretching direction (MD) and the heat shrinkage in the transverse direction (TD) of the high-temperature resistant separator. In addition, in the high-temperature resistant separator according to the other embodiment, the ratio of the heat shrinkage in the main stretching direction to the heat shrinkage in the transverse direction tends to approach 1. Therefore, the high-temperature resistant separator is less likely to be curled due to the mismatch in the shrinkage stress direction, and is less likely to increase the risk of electrode contact.

[0034] In another embodiment of the high temperature resistant separator, the melt rupture temperature of the high temperature resistant separator is greater than 280° C., preferably greater than 300° C. The melt rupture temperature of a conventional ceramic separator with a heat strengthening layer that does not have a cross-linked composite structure on the surface is only 150° C. to 170° C. Therefore, the high temperature resistant separator of the present invention can maintain melt integrity even at extremely high temperatures.

[0035] In another embodiment of the high-temperature resistant separator, the polyolefin porous substrate is a single-layer or multi-layer porous substrate of polyethylene, polypropylene, or a copolymer thereof. Examples include, but are not limited to, single-layer polyethylene, single-layer polypropylene, two-layer polyethylene / polypropylene, or three-layer polypropylene / polyethylene / polypropylene. In one embodiment of the present invention, the polyolefin porous substrate may have a thickness of about 5 μm to 30 μm, preferably 7 μm to 25 μm, and a porosity of about 30% to 60%.

[0036] In another embodiment of the high-temperature resistant separator, the inorganic layer is formed on one or both surfaces of the polyolefin porous substrate, the inorganic particles content in the inorganic layer is 80-99 wt%, and the adhesive content is 1-20 wt%. The high-temperature resistant separator according to the present invention may be an inorganic layer on one or both sides, preferably a coating layer on both sides, with a thickness of 0.5 μm-5 μm, preferably 0.5 μm-3 μm.

[0037] In another embodiment of the high-temperature resistant separator, the inorganic particles are Al2O3, Al(OH)3, boehmite (AlOOH), TiO2, SiO2, Mg(OH)2, BaSO4, BaTiO3, SrTiO3, HfO2, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, SiC, B4C, AlN, BN, Si3N4, TiN, or a combination thereof. Since the size of the gap formed between the inorganic particles affects the battery characteristics, if the particle size of the inorganic particles is too large, the gap between the particles may be too large, which may easily cause a short circuit due to lithium dendrites. Therefore, the average particle size (D50) of the inorganic particles may be 0.1 μm to 2.0 μm, and preferably 0.2 μm to 1.0 μm.

[0038] As an adhesive suitable for the inorganic layer of the porous membrane, those suitable for the field of separators having carbon bonds containing hydrogen atoms can be used. For example, adhesives having properties such as high electrochemical stability, excellent wettability and chemical resistance to electrolytes are known. In another embodiment of the high-temperature resistant separator, the adhesive is ethylene-vinyl acetate copolymer (EVA), poly(meth)acrylate, crosslinkable (meth)acrylic resin, polyacrylamide (PAM), fluorine-based rubber, styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyvinylpyrrolidone (PVP), poly-N-vinylacetamide, polyvinylidene fluoride (PVDF), polyurethane, or a combination thereof.

[0039] Another aspect of the present invention provides a method for producing a high-temperature resistant separator. The method includes providing a porous membrane, preparing a thermally strengthened precursor solution, applying the thermally strengthened precursor solution to the porous membrane, and irradiating ultraviolet light to form a thermally strengthened layer on the surface of the porous membrane and the inner wall of the porous structure. The porous membrane has a polyolefin porous substrate and an inorganic layer. The inorganic layer includes a plurality of inorganic particles and an adhesive. The inorganic layer is formed on at least one surface of the polyolefin porous substrate. The polyolefin porous substrate and the inorganic layer have a plurality of porous structures that are connected to each other. The thermally strengthened precursor solution includes 600 ppm to 3000 ppm of titanium alkoxide and 150 ppm to 1500 ppm of photoreactive agent. The thermally strengthened layer is a composite layer formed by crosslinking the titanium alkoxide and the photoreactive agent with the polyolefin and / or the adhesive on the surface of the porous membrane and the inner wall of the porous structure.

[0040] In the method for preparing a high-temperature resistant separator according to the present invention, the titanium alkoxide in the thermally strengthened precursor solution is methanol titanium, ethanol titanium, isopropanol titanium or a combination thereof, and the solvent is methanol, ethanol, isopropanol or a combination thereof. The concentration of the titanium alkoxide in the thermally strengthened precursor solution is 600 ppm to 3000 ppm, preferably 600 ppm to 2500 ppm.

[0041] In the method for preparing a high-temperature resistant separator according to the present invention, the photoreactive agent in the thermally strengthened precursor solution is 2-isopropylthioxanthone, thioxanthone, thioxanthone derivatives or combinations thereof. The concentration of the photoreactive agent in the thermally strengthened precursor solution is 150 ppm to 1500 ppm, preferably 150 ppm to 1000 ppm.

[0042] In the method for preparing the high-temperature resistant separator according to the present invention, the heat strengthening precursor solution further comprises a crosslinking coagent to strengthen the physical structure of the heat-stabilized film. Suitable crosslinking coagents for the heat strengthening precursor solution of the present invention are divinylbenzene, bisphenol A dimethyl acrylate, bisphenol A epoxy diacrylate, triallyl cyanurate, triallyl isocyanurate, quaternary pentaerythritol triallyl ether, butadiol diacrylate, ethylene glycol diacrylate, or combinations thereof. In one embodiment of the present invention, the concentration of the crosslinking coagent is 100 ppm to 2000 ppm.

[0043] In one embodiment of the high-temperature resistant separator, the ultraviolet light required to form the thermal strengthening layer has a wavelength of 340 nm to 460 nm and an irradiation dose of 10 mJ / cm 2 ~1000mJ / cm 2 It is.

[0044] In one embodiment of the high-temperature resistant separator, the method for forming the thermally strengthened layer on the surface of the porous membrane and the inner wall of the porous structure can be a spray method, a dip method, a roll coating method, a doctor blade coating method or a slit coating method.

[0045] In the high-temperature resistant separator according to an embodiment, the heat-strengthening layer may further include additives such as antistatic agents, flame retardants, antioxidants, or surface modifiers, if necessary.

[0046] The following examples are presented to further illustrate the present invention, but are not intended to limit the scope of the invention.

[0047] Working Example

[0048] Preparation Example: Preparation of Inorganic Particle Coating Solution

[0049] 38 g of aluminum oxide (CQ-030EN, purchased from Shandong China Porcelain Functional Materials Co., Ltd.), 3.4 g of polyacrylic acid ester, 0.68 g of ammonium polyacrylate (BYK-154, solid content 42%, purchased from BYK, Germany), 0.13 g of polyether-modified silicone surfactant (BYK-349, purchased from BYK, Germany) and 52.9 g of deionized water were mixed and stirred uniformly to obtain an inorganic particle coating solution.

[0050] Preparation Example: Preparation of Porous Membrane

[0051] The obtained inorganic particle coating liquid was applied to two different surfaces of a 9 μm-thick polyethylene porous substrate (porosity 48%) and dried, and then a 2 μm-thick inorganic layer was formed on each of the two different surfaces of the polyethylene porous substrate to obtain a porous membrane.

[0052] Example 1: Preparation of high-temperature resistant separator

[0053] 250 mg of titanium isopropanol and 25 mg of 2-isopropylthioxanthone were added to 100 g of isopropanol, and the mixture was stirred uniformly at room temperature to obtain a thermally strengthened precursor solution.

[0054] The porous membrane prepared in the preparation example was immersed in the thermal strengthening precursor solution for 30 seconds by the impregnation coating method, taken out, excess liquid on the surface was removed, and the membrane was dried at 60°C for 5 minutes. Then, it was irradiated with 500 mJ / cm in an air environment. 2 The film was exposed to a UV lamp with a wavelength of 360 nm to obtain a high-temperature resistant separator having a porous film and a heat-strengthened layer with a crosslinked structure on the surface of the porous structure.

[0055] The physical properties and thermal stability of the obtained high-temperature resistant separator were measured by the measurement methods described below. The measurement results are shown in Table 1.

[0056] Measurement of air permeability (Gurley): According to the ASTM D-726 standard, the high-temperature resistant separator to be measured was cut into a size of 1 square inch, and the time required for 100 cc of air to pass through the high-temperature resistant separator to be measured was measured using a Gurley air permeability meter to obtain the air permeability.

[0057] Tensile strength measurement: According to ASTM D882-09 standard, the high-temperature resistant separator to be measured was cut into a size of ≥150 mm in length and ≥10 mm in width along the main stretching direction (MD), and pulled at a speed of 500 mm / min using a universal tensile machine to obtain the maximum load value when the sample broke. Then, it was divided by the cross-sectional area of ​​the high-temperature resistant separator (sample width x substrate thickness) to calculate the tensile strength of the high-temperature resistant separator in the MD and TD directions.

[0058] Puncture strength measurement and high-temperature puncture strength: Based on the ASTM D2582 standard, the obtained high-temperature resistant separator was punctured into the sample to be measured using a tensile machine (MSG-5, purchased from Kato Tech, Japan) with a round head stainless steel needle with a needle diameter of 1 mm and R angle of 0.5 mm at a test speed of 100±10 mm / min, and the maximum force required to puncture and break the high-temperature resistant separator was recorded as the initial puncture strength (S0). The high-temperature resistant separator was then heated at 150°C for 1 hour, and after heating, the high-temperature puncture strength was measured in the same manner as above, and the maximum force required to puncture and break the high-temperature resistant separator was recorded as the high-temperature puncture strength (S1).

[0059] Heat shrinkage measurement: A 10cm x 10cm sample was cut, and the initial lengths M0 and T0 in the main stretch direction (MD) and transverse direction (TD) were marked at the center of the sample before measurement. After marking, the sample was sandwiched between two A4 sheets of paper and placed in an oven, heated at 180°C for 1 hour, and after heating was completed, the sample was cooled and the length M1 in the main stretch direction (MD) and the length T1 in the transverse direction (TD) at the center of the sample were measured. Heat shrinkage in the main stretching direction (MD) = (M0-M1) / M0 x 100% Thermal shrinkage rate in the transverse direction (TD) = (T0 - T1) / T0 x 100% When it was impossible to perform a measurement to obtain a value for the thermal shrinkage rate due to serious curl deformation or even rupture, the sample was judged as "NG."

[0060] Melt rupture temperature: A sample of the high-temperature resistant separator with a length of 8 mm and a width of 4.5 mm was cut and placed in the sample chamber of a thermomechanical analyzer (TMA 450, purchased from TA Instruments, USA). The sample was heated to 350°C at a rate of 5°C / min under a load of 0.01N in a nitrogen atmosphere, and the melt rupture temperature was recorded after the measurement was completed. Here, under a fixed load of 0.01N, the high-temperature resistant separator reached its heat-bearing limit with the increase in temperature, and was judged to have broken when the deformation reached its maximum value. This rupture temperature point was defined as the melt rupture temperature.

[0061] High temperature crack test: Cut out a 10cm x 10cm separator sample and place it in a 250°C oven for 1 hour. After taking it out, visually check whether there are any cracks. "X" indicates that there are cracks or that the separator is severely curled, deformed, fractured, and incomplete, making it impossible to judge, and "○" indicates that there are no cracks.

[0062] Example 2: Preparation of high-temperature resistant separator

[0063] A high-temperature resistant separator including a thermally strengthened layer was prepared according to the method of Example 1, except that the thermally strengthened precursor solution was replaced with a thermally strengthened precursor solution prepared by adding 125 mg of titanium isopropanol and 50 mg of 2-isopropylthioxanthone to 100 g of isopropanol.

[0064] The physical properties and thermal stability of the obtained high-temperature resistant separator were measured by the measurement methods described in Example 1. The measurement results are shown in Table 1.

[0065] Example 3: Preparation of high-temperature resistant separator

[0066] A high-temperature resistant separator including a thermally strengthened layer was prepared according to the method of Example 1, except that the thermally strengthened precursor solution was replaced with a thermally strengthened precursor solution prepared by adding 250 mg of titanium isopropanol and 50 mg of 2-isopropylthioxanthone to 100 g of isopropanol.

[0067] The physical properties and thermal stability of the obtained high-temperature resistant separator were measured by the measurement methods described in Example 1. The measurement results are shown in Table 1.

[0068] Example 4: Preparation of high-temperature resistant separator

[0069] A high-temperature resistant separator having a thermal strengthening layer was prepared according to the method of Example 1, except that the thermal strengthening precursor solution was replaced with a thermal strengthening precursor solution prepared by adding 250 mg of titanium isopropanol and 100 mg of 2-isopropylthioxanthone to 100 g of isopropanol.

[0070] The physical properties and thermal stability of the obtained high-temperature resistant separator were measured by the measurement methods described in Example 1. The measurement results are shown in Table 1.

[0071] Example 5: Preparation of high-temperature resistant separator

[0072] A high-temperature resistant separator including a thermally strengthened layer was prepared according to Example 1, except that the thermally strengthened precursor solution was replaced with a thermally strengthened precursor solution obtained by adding 250 mg of titanium isopropanol, 50 mg of 2-isopropylthioxanthone, and 75 mg of triallyl isocyanurate to 100 g of isopropanol and stirring the mixture uniformly at room temperature.

[0073] The physical properties and thermal stability of the obtained high-temperature resistant separator were measured by the measurement methods described in Example 1. The measurement results are shown in Table 1.

[0074] Comparative Example 1: Preparation of separator

[0075] In Comparative Example 1, the physical properties and thermal stability of the porous membrane of the preparation example were measured according to the measurement methods described in Example 1. The measurement results are shown in Table 1.

[0076] Comparative Example 2: Preparation of separator

[0077] 25 mg of 2-isopropylthioxanthone was added to 100 g of isopropanol and stirred uniformly at room temperature to obtain a photoreactant solution. The porous membrane of the preparation example was immersed in the photoreactant solution for 30 seconds by the impregnation coating method, taken out, excess liquid on the surface was removed, and the membrane was dried at 60°C for 5 minutes. After that, it was irradiated with the same wavelength of 360 nm and irradiation dose of 500 mJ / cm in an air environment. 2 The film was exposed to a UV lamp to obtain an isolating film.

[0078] The physical properties and thermal stability of the obtained separator were measured by the measurement methods described in Example 1. The measurement results are shown in Table 1.

[0079] Comparative Example 3: Preparation of separator

[0080] A separator was prepared according to the procedure of Comparative Example 2, except that the photoreactor solution obtained by adding 50 mg of 2-isopropylthioxanthone to 100 g of isopropanol and mixing them uniformly was omitted.

[0081] The physical properties and thermal stability of the obtained separator were measured by the measurement methods described in Example 1. The measurement results are shown in Table 1.

[0082] Comparative Example 4: Preparation of separator

[0083] In Comparative Example 4, the porous membrane of the preparation example was used, but it was immersed in a titanium alkoxide solution prepared by adding 250 mg of titanium isopropanol to 100 g of isopropanol for 30 seconds, then removed to remove excess liquid on the surface, and dried at 60°C for 5 minutes to obtain an isolation membrane.

[0084] The physical properties and thermal stability of the obtained separator were measured by the measurement methods described in Example 1. The measurement results are shown in Table 1. Table 1: Measurement results of physical properties and heat resistance of separators of Examples 1 to 5 and Comparative Examples 1 to 4 [Table 1]

[0085] As can be seen from the properties shown in Table 1, after the separator according to Examples 1 to 5 of the present invention is left at 180°C, which is higher than the melting point of the known polyolefin material, for 1 hour, the heat shrinkage rate in the main direction (MD) or the transverse direction (TD) is less than 0.5%, and the MD / TD ratio tends to approach 1. This indicates that the heat shrinkage of the original membrane material has already been suppressed, and curl deformation due to the mismatch of shrinkage stress in each direction is difficult to occur. At the same time, the melt rupture temperatures are all higher than 309°C. Compared with Comparative Examples 1 to 4, the high-temperature resistant separator according to the present invention can simultaneously have low heat shrinkage in each direction, puncture resistance after high-temperature heating, high melt rupture temperature, and high-temperature structural integrity of the inorganic layer containing the polyolefin porous substrate and inorganic particles. Referring to Figures 1a and 1b, these are the appearance images of the separator after the 250°C high-temperature crack test in Comparative Example 1 and Comparative Example 3, respectively. As shown in FIG. 1a and FIG. 1b, the separator of Comparative Example 1 and the separator of Comparative Example 3 both have serious problems of curling deformation and cracking, and are unable to provide an insulating effect for the electrode under high temperatures. Referring to FIG. 2, this is an appearance image of the high-temperature resistant separator of Example 3 of the present invention after a high-temperature crack test at 250°C. As shown in FIG. 2, the high-temperature resistant separator of Example 3 not only has no curling deformation, but also maintains the integrity of the membrane body. In addition, the low concentration of titanium alkoxide and the photoreactive agent added are used for induction to crosslink with the polyolefin porous substrate in which the porous membrane surface is not completely covered with the inorganic layer, and the adhesive on the porous membrane surface or in the inorganic layer to form a composite heat-strengthened layer. Therefore, the heat-strengthened layer of the high-temperature resistant separator of the present invention does not affect the existing breathability of the separator itself, and does not cause an increase in internal electrical resistance after the battery is assembled. Therefore, the high-temperature resistant separator of the present invention can sufficiently improve the heat resistance and dimensional stability of the polyolefin-based separator when the temperature is higher than the melting point, and can continue to provide battery protection at high temperatures without affecting the ionic conductivity at room temperature.

[0086] Although the present invention has been disclosed in the above embodiments, they are not used to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention is subject to the scope of the claims attached below.

Claims

1. A high temperature resistant separator, A porous membrane having a polyolefin porous substrate and an inorganic layer; a thermally strengthened layer formed on the surface of the porous membrane and on the inner wall of the porous structure; Including, The inorganic layer contains a plurality of inorganic particles and an adhesive, and is formed on at least one surface of the polyolefin porous substrate, and the polyolefin porous substrate and the inorganic layer have a plurality of porous structures that are mutually connected; The heat strengthening layer is a composite layer formed by crosslinking titanium alkoxide and a photoreactive agent with polyolefin and / or adhesive on the surface of the porous membrane and the inner wall of the porous structure.

2. 2. The high temperature resistant separator of claim 1, wherein the titanium alkoxide is methanol titanium, ethanol titanium, isopropanol titanium, or a combination thereof.

3. 2. The high-temperature resistant separator according to claim 1, wherein the titanium alkoxide has a concentration of 600 ppm to 3000 ppm.

4. 2. The high-temperature resistant separator according to claim 1, wherein the concentration of the photoreactive agent is 150 ppm to 1500 ppm.

5. The high-temperature resistant separator of claim 1 , wherein the photoreactor is 2-isopropylthioxanthone, thioxanthone, a thioxanthone derivative, or a combination thereof.

6. 2. The high-temperature resistant separator according to claim 1, wherein the heat shrinkage in each direction after being left at 180° C. for 1 hour is less than 1%.

7. The high-temperature resistant separator according to claim 1 , wherein the polyolefin porous substrate is a single-layer or multi-layer porous substrate made of polyethylene, polypropylene or a copolymer thereof.

8. 2. The high-temperature resistant separator according to claim 1, wherein the content of the inorganic particles in the inorganic layer is 80 to 99% by weight, and the content of the adhesive is 1 to 20% by weight.

9. The inorganic particles are Al 2 O 3 , Al(OH) 3 , boehmite (AlOOH), TiO 2 , SiO 2 , Mg(OH) 2 , BaSO 4 , BaTiO 3 , SrTiO 3 , HfO 2 , SnO 2 , CeO 2 , MgO, NiO, CaO, ZnO, ZrO 2 , SiC, B 4 C, AlN, BN, Si 3 N 4 , TiN, or a combination thereof.

10. 2. The high-temperature resistant separator according to claim 1, wherein the adhesive is selected from the group consisting of ethylene-vinyl acetate copolymer (EVA), poly(meth)acrylate, cross-linkable (meth)acrylic resin, polyacrylamide (PAM), fluororubber, styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyvinylpyrrolidone (PVP), poly N-vinylacetamide, polyvinylidene fluoride (PVDF), polyurethane, and combinations thereof.

11. The high temperature resistant separator according to claim 1 , wherein the heat strengthening layer further comprises a cross-linking coagent.

12. 12. The high temperature resistant separator according to claim 11, wherein the cross-linking coagent is divinylbenzene, bisphenol A dimethyl acrylate, bisphenol A epoxy diacrylate, triallyl cyanurate, triallyl isocyanurate, pentaerythritol triallyl ether, butadiol diacrylate, ethylene glycol diacrylate, or a combination thereof.